Influence of ECAP processing temperature and number of passes on hardness and microstructure of Al-6063. (31st October 2022) - Gupta, Akash; Saxena, K. K.; Bharti, Ajaya; Lade, Jayahari; Chadha, Kanwal; Paresi, Prudvi Reddy
ABSTRACT: Equal-channel angular pressing (ECAP) is one the most efficient techniques of severe plastic deformation for grain refinement and improving mechanical properties. In this study, aluminium alloy 6063 is used due to its wide range of applications. The ECAP process depends on die geometry, number of passes, processing temperature, following routes, plunger speed, strain and frictions. In this study, cylindrical billets of Al-6063 are processed at two different temperatures, at room temperature and at elevated temperature (250°C) through route BC. In the present research, specimens deformed after first pass, third pass and the sixth pass are considered for analysing the microstructure evolution and hardness values. Optical microscopy and electron back scattered diffraction (EBSD) techniques are used for microstructural study. Hardness test is carried out for hardness measurement with test load 100 g. The hardness is increased up to 85 HV after six passes at room temperature. Hardness increases up to 83% only after one pass at room temperature. EBSD result shows the low-angle grain boundaries are 91.06% where high-angle grain boundaries are only 8.9% of sample with one pass at 250°C. The elevated processing temperature influences both hardness and microstructure.